Phosphatidylserine translocation, cholesterol spatial distribution, and acrosome reaction reliably distinguish sperm capacitation from cryoinjury in bovine sperm - Garcia-Oliveros, Laura Nataly; Bozzi, Alexandre da Rocha; Cardoso Silva, Thais de Oliveira; Baatsch Nascimento, Fernanda; Oliveira, Thainara Rodrigues de; Miguel, Ellen Lara; Alves, Maíra Bianchi Rodrigues [UNESP]; Rangel, Raissa Braido [UNESP]; Andrade, André Furugen Cesar de; Arruda, Rubens Paes de; Kerns, Karl; Celeghini, Eneiva Carla Carvalho (Elsevier, 2025)
Sperm capacitation is a critical process for successful fertilization, involving multiple regulated cellular changes. On the other hand, cryopreservation induces membrane changes that can mimic capacitation, potentially leading to misinterpretation of sperm function. Distinguishing true capacitation from cryoinjury remains challenging, as both share surface markers despite involving distinct mechanisms and impacts on fertilization. This study aimed to assess the effectiveness of various techniques in detecting key capacitation-related events and differentiating them from cryopreservation-induced injuries. Semen samples from twelve bulls (three ejaculates each; n = 36) were collected and divided into control (CO) and in vitro capacitated (CAP) groups. All samples were analyzed for sperm concentration, motility characteristics, and capacitation-associated events - including membrane lipid disorder, lipid peroxidation, phosphatidylserine translocation, cholesterol redistribution, acrosome reaction, and mitochondrial membrane potential. Following the initial analysis, semen was cryopreserved, thawed, and then split into cryopreserved control (CRYCO) and capacitated (CRYCAP) groups for reanalysis. Data were evaluated using ANOVA, with means compared by Tukey's test (significance level ≤5 %). Correlations among all measured variables were also examined. Capacitation induction decreased curvilinear velocity, while increasing straightness, phosphatidylserine translocation, cholesterol efflux, and acrosome-reacted sperm, regardless of cryopreservation status. In contrast, plasma membrane disorganization and lipid peroxidation were markedly elevated, and cholesterol redistribution was reduced after cryopreservation. Notably, a strong positive correlation was observed between phosphatidylserine translocation and acrosome reaction in both fresh and cryopreserved sperm. In conclusion, phosphatidylserine translocation, cholesterol spatial distribution, and the acrosome reaction were the most reliable markers for distinguishing true capacitation from cryoinjury.